Development of Defensive Actions in Small-Sided and Conditioned Games With Offensive Purposes in Futsal - Pizarro, David; Práxedes, Alba; Travassos, Bruno; Moreno, Alberto (Frontiers in Psychology, 2020)
Based on ecological dynamics approach, nonlinear pedagogy (NLP) have emerged with the goal to promote a holistic approach through the use of Small-Sided and Conditioned Games (SSCGs), to optimize specific tactical defensive and offensive behaviours of players. This study analysed the indirect effects of an intervention program, based on NLP (task design based on tactical principles of attack and numerical advantage of attacking team), in decision making (DM) and execution (Ex) in defensive technical-tactical actions in U16 futsal. 8 futsal players (U16 years) participated in 12 training session, spread over two phases: pre-intervention and intervention. The Game Performance Evaluation Tool (GPET) instrument was used to analyse the DM and Ex of 2600 defensive actions measured during competitive matches. Results shown significant improvements in marking actions (to the player with the ball: DM, p = .001; Ex, p = .001; and to the player without the ball: DM, p = .039; Ex, p = .046); improvements in blocking actions (DM, p=.015); and improvements in help-coverage actions (Ex, p=.014). No significant differences were found in the interception and tackling actions. This study has shown evidence that the NLP approach is an appropriate theoretical framework to enhance acquisition of defensive tactical behaviour in futsal. However, not all actions improved. Therefore, coaches should design representative tasks to optimally develop technical-tactical training processes based on the phases of futsal game (offensive and defensive) and considering the level of opposition.